2022
DOI: 10.1002/adem.202200844
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanocomposites Based on TiO2as a Reinforcing Agent: An Overview

Abstract: Titania (TiO2) is one of the most versatile materials in the field of polymer science and technology. In recent years, a large area of research has focused on the combination of TiO2 with polymers and other carbon nanostructures. Literature reports suggest that nanoscale TiO2 reinforcement gives rise to new optical, electrical, and physiochemical properties attained at extremely low TiO2 content, thus making these nanocomposites (NCs) a promising new class of materials. This review summarizes the contemporary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 239 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…The sorption reaction is thought to be spontaneous based on the negative values of G°, which fall within the same range from -36.806 to − 42.089 kJ mol -1 . (10) log q e = log K F + 1 n log C e www.nature.com/scientificreports/ Lu et al, 2018, report the relationship between the temperature and the absolute G values. Generally, the following order is supported by the experimental results for the pH effect, kinetics (Tables 3), isotherms (Table 4), and thermodynamics (absolute values of H°, S°, and G° (Table 6)): S 3 > S 2 > S 3.…”
Section: Effect Of Temperature and Thermodynamic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sorption reaction is thought to be spontaneous based on the negative values of G°, which fall within the same range from -36.806 to − 42.089 kJ mol -1 . (10) log q e = log K F + 1 n log C e www.nature.com/scientificreports/ Lu et al, 2018, report the relationship between the temperature and the absolute G values. Generally, the following order is supported by the experimental results for the pH effect, kinetics (Tables 3), isotherms (Table 4), and thermodynamics (absolute values of H°, S°, and G° (Table 6)): S 3 > S 2 > S 3.…”
Section: Effect Of Temperature and Thermodynamic Studiesmentioning
confidence: 99%
“…The focus of recent research on polymer nanocomposite for the removal of water contaminants [7][8][9][10][11] . Clays and silicates are used as inorganic nanofillers due to their low cost, high aspect ratio, rich intercalation chemistry, high strength, stiffness, and thermal stability of polymers [12][13][14][15] .…”
mentioning
confidence: 99%
“…Apart from ZnO, there exist other metal oxide materials that can be used as nanofillers such as TiO 2 , Fe 2 O 3 , Al 2 O 3 , NiO, and SnO 2 [29][30][31][32]. Among these metal oxides, a combination of TiO 2 and ZnO as a nanofiller is used with several polymers and polymeric nanocomposites for multifunctional applications [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, practical application of TiO 2 is hindered by its recombination rate and low absorbance. A lot of efforts have been made by researchers to overcome these issues by adopting various strategies, including doping TiO 2 with other metal/metal oxide polymers, surface sensitization, and so on. Several scientific studies have demonstrated that self-doping of the same cation in pristine catalysts can enhance photocatalytic activity by tuning the electronic structure and extending the photoresponse range, thereby improving the photocatalytic activity of semiconductors without introducing foreign elements .…”
Section: Introductionmentioning
confidence: 99%